Preparation method of high-performance flexible thermoelectric film

CN117355200BActive Publication Date: 2026-10-27NINGBO UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311116978.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-01
Publication Date
2026-10-27
Estimated Expiration
2043-09-01

AI Technical Summary

Technical Problem

不幸的是,一维材料的湿法化学合成导致热电薄膜应用更加复杂、成本高

Benefits of technology

[0020]1)本发明制备方法的工艺简单便捷,在整个制备过程中无需添加任何浆料溶剂和有机溶剂,无有毒气体排放,对环境友好,且使用的材料及设备易于获得,生产成本低,利于量产;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117355200B_ABST
    Figure CN117355200B_ABST
Patent Text Reader

Abstract

The preparation method of the high-performance flexible thermoelectric film comprises the following steps: crushing bulk thermoelectric material to obtain thermoelectric material powder; uniformly mixing the thermoelectric material powder and a PTFE binder by using a mixer to obtain mixture A, wherein the addition ratio of the PTFE binder is 0.5-10wt%; putting the mixture A into a planetary ball mill for mixing and stirring for 5-10 min, and controlling the rotating speed at 200-300r / min to obtain a fiberized mixture B; extruding and forming the fiberized mixture B on a vertical pair of rollers by using a vertical hot pressing roller to obtain a thermoelectric film with a thickness of 300-500mu; and horizontally rolling the thermoelectric film by using a horizontal hot rolling roller to obtain a flexible thermoelectric film with a thickness of 50-150mu. The preparation method is simple and convenient, low in cost, and beneficial to mass production; the prepared film has high mechanical flexibility and high room-temperature thermoelectric performance, and has high density, and is expected to be applied to human-wearable thermoelectric power generation devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of thermoelectric thin films and their preparation, and particularly relates to a method for preparing a high-performance flexible thermoelectric thin film. Background Technology

[0002] With the increasing demand for wearable power sources from the Internet of Things (IoT), flexible thermoelectric films, with their unique wearability and scalability advantages, have attracted growing attention in wearable electronics. Typically, flexible thermoelectric films are composed of organic materials with intrinsically high flexibility, but their relatively poor electrical transport properties and low power factor make it difficult to achieve high thermoelectric performance. In contrast, inorganic thermoelectric films generally exhibit high Seebeck coefficients, high electrical conductivity, and low thermal conductivity; however, their inherent rigidity and brittleness make them susceptible to mechanical deformations such as stretching and torsion, resulting in very limited mechanical freedom and significantly restricting their potential as flexible wearable devices. Therefore, obtaining thermoelectric materials that possess both excellent flexibility and high thermoelectric performance remains a challenge for flexible wearable thermoelectric devices.

[0003] Currently, there are two main methods for preparing inorganic thermoelectric thin films: magnetron sputtering and wet chemical methods combined with vacuum-assisted filtration. While depositing thermoelectric thin films on flexible organic substrates can improve the flexibility of devices, these high-vacuum deposition techniques are difficult to mass-produce due to their high cost and low production efficiency. Furthermore, the flexibility of the film is limited by the substrate and the thickness of the thermoelectric film, and the flexibility gained by depositing very thin films does not change the inherent rigidity and brittleness of these inorganic thermoelectric materials. Traditional wet chemical methods also have their limitations; to ensure film flexibility, they are limited to using some low-dimensional materials, especially one-dimensional materials, such as nanowires and nanoribbons. Unfortunately, the wet chemical synthesis of one-dimensional materials makes the application of thermoelectric thin films more complex and costly. Given the limitations of high-vacuum deposition and wet chemical methods, developing a method for preparing thermoelectric thin films that combine high thermoelectric performance and excellent flexibility is crucial, and this is of great significance for the development of high-performance, fully flexible thermoelectric generators. Summary of the Invention

[0004] The technical problem to be solved by the present invention is to provide a simple, convenient, and low-cost method for preparing high-performance flexible thermoelectric thin films, which addresses the shortcomings of the prior art. The prepared thin films have both high mechanical flexibility and high room temperature thermoelectric properties, and high density, and are expected to be used in wearable thermoelectric power generation devices.

[0005] The technical solution adopted by this invention to solve the above-mentioned technical problems is as follows: a method for preparing a high-performance flexible thermoelectric thin film, comprising the following steps:

[0006] (1) The bulk thermoelectric material is crushed and ground into powder using a planetary ball mill. The powder particles are less than 5μm to obtain thermoelectric material powder.

[0007] (2) The obtained thermoelectric material powder and PTFE binder are mixed evenly with a mixer to obtain mixture A, wherein the proportion of PTFE binder added to mixture A is 0.5-10 wt%.

[0008] (3) Put the mixture A into a planetary ball mill and mix for 5-10 minutes. The speed is controlled at 200-300 r / min. The polytetrafluoroethylene in the PTFE binder is fiberized into long fibers with a diameter of 1-100 nm and a length of 10-20 μm to obtain fiberized mixture B.

[0009] (4) The obtained fibrous mixture B is extruded on a vertical roller press through a vertical hot press to obtain a thermoelectric film with a thickness of 300-500 μm.

[0010] (5) The thermoelectric film obtained in step (4) is further rolled into a flexible thermoelectric film with a thickness of 20-150 μm by a horizontal hot rolling roll.

[0011] This invention involves mixing, dispersing, and shearing thermoelectric materials and PTFE binders, transforming the PTFE binder from a loose state to a spiderweb-like state. The PTFE network structure then wraps and connects the powder particles of the thermoelectric material, resulting in a tight bond between the binder and the powder particles. This effectively solves the problem of poor flexibility in inorganic thermoelectric films. While improving flexibility, it also facilitates carrier migration in the thermoelectric material, maintaining the thermoelectric properties of the material itself. The resulting film exhibits good toughness and high density.

[0012] Preferably, the thermoelectric material is a sulfide-based thermoelectric material. More preferably, the sulfide-based thermoelectric material is Bi. 0.5 Sb 1.5 Te3, AgSbTe2, Cu 25 As 35 Se6Te 34 One of Ag2Te.

[0013] Preferably, in step (1), the rotational speed of the planetary ball mill is 250-520 r / min, and the mixing time is 3-10 h.

[0014] Preferably, in step (2), the speed of the mixer is 100-10000 r / min and the mixing time is 0.5-30 min.

[0015] Preferably, in step (2), the temperature inside the mixer is 5-45℃.

[0016] Preferably, in step (2), the temperature inside the mixer is 5-30℃.

[0017] Preferably, in step (4), the gap width between the two vertical hot press rollers is 0-2μm, the temperature of the two vertical hot press rollers is 20-100℃, and the pressure is 0-50t.

[0018] Preferably, in step (5), the gap width between the two horizontal hot rolling rolls is 0-2μm, the temperature of the two horizontal hot rolling rolls is 100-150℃, and the pressure is 0-50t.

[0019] Compared with the prior art, the present invention has the following advantages:

[0020] 1) The preparation method of the present invention is simple and convenient. No slurry solvent or organic solvent needs to be added during the entire preparation process. There is no toxic gas emission, which is environmentally friendly. The materials and equipment used are easy to obtain, the production cost is low, and it is conducive to mass production.

[0021] 2) This invention mixes, disperses, and shears the thermoelectric material and PTFE binder to transform the PTFE binder into a network structure. The network structure of the PTFE binder softens during hot pressing and wraps around and connects the powder particles of the thermoelectric material. Thus, the network structure of the PTFE binder is tightly bonded to the powder particles of the thermoelectric material, which effectively improves the flexibility of the thermoelectric film while ensuring that the thermoelectric film has a high density.

[0022] 3) The thin film prepared by the method of the present invention has both high mechanical flexibility and high room temperature thermoelectric properties, and is expected to be used in wearable thermoelectric power generation devices. Attached Figure Description

[0023] Figure 1 This is a SEM image of the cross-section of the thermoelectric thin film prepared in Example 1;

[0024] Figure 2 This is an AFM test image of the surface of the thermoelectric thin film prepared in Example 1;

[0025] Figure 3 The temperature-dependent thermoelectric properties of the thermoelectric thin film prepared in Example 1 are shown in the graph.

[0026] Figure 4 The results are the performance cycle stability test results of the thermoelectric thin film prepared in Example 1. Detailed Implementation

[0027] To better understand the present invention, the following detailed description is provided in conjunction with embodiments. However, the implementation of the present invention is not limited thereto. For process parameters not specifically described, conventional techniques can be referred to.

[0028] The method for preparing the high-performance flexible thermoelectric thin film in Example 1 includes the following steps:

[0029] (1) Preparation of thermoelectric materials:

[0030] The molar composition of chalcogenide thermoelectric materials is represented by the chemical formula Bi. 0.5 Sb 1.5 The preparation method of Te3 includes the following steps: using Bi, Sb, and Te elements of 4N purity as raw materials, weighing and mixing them uniformly according to the required weight in a glove box filled with inert gas; loading the uniformly mixed material into a pre-cleaned 9mm aperture quartz tube, and evacuating the quartz tube to a vacuum of 1.0 × 10⁻⁶. -3 After Pa, the mixture was sealed using an oxyhydrogen flame. The sealed quartz tube containing the mixture was placed in a oscillating furnace and slowly heated to 700°C at a rate of 1°C / min. The temperature was maintained at this point for 5 hours while oscillating. After melting, the tube was cooled with the furnace. Once the furnace temperature reached room temperature, the quartz tube was removed and broken to obtain Bi. 0.5 Sb 1.5 Te3 bulk thermoelectric material;

[0031] (2) Change Bi 0.5 Sb 1.5 Te3 bulk thermoelectric material was pulverized and ground into powder using a ball mill at 300 r / min for 3 h, resulting in powder particles smaller than 5 μm, to obtain Bi. 0.5 Sb 1.5 Te3 thermoelectric material powder;

[0032] (3) The obtained Bi 0.5 Sb 1.5 Te3 thermoelectric material powder and PTFE binder are mixed evenly in a mixer to obtain mixture A, wherein the proportion of PTFE binder added to mixture A is 0.5 wt%.

[0033] (4) Mix A in a planetary ball mill for 5 minutes, with the speed controlled at 250 r / min, to fiberize the polytetrafluoroethylene in the PTFE binder into long fibers with a diameter of 1-100 nm and a length of 10-20 μm, to obtain fiberized mixture B.

[0034] (5) The obtained fibrous mixture B is passed through a vertical hot press roller at 80°C on a vertical roller mill and extruded under a pressure of 15t to obtain a thermoelectric film with a thickness of 300μm.

[0035] (6) The thermoelectric film obtained in step (4) is further passed through a horizontal hot rolling mill at 120°C and rolled multiple times under a pressure of 35t to form a flexible thermoelectric film of Example 1 with a thickness of 50μm.

[0036] Morphology testing: Using scanning electron microscopy (SEM) to observe the cross-section of the flexible thermoelectric film of Example 1, it can be seen that the polytetrafluoroethylene has been fiberized into long fibers with a diameter of less than 100 nm and a length of approximately 20 μm. (See...) Figure 1 This long fiber structure ensures the toughness and tensile strength of the thermoelectric film.

[0037] Height distribution: The height distribution of the flexible thermoelectric thin film prepared in Example 1 was measured using atomic force microscopy (AFM), see [reference needed]. Figure 2 Analysis revealed that its average surface roughness was 42 nm, indicating that the hot calendering process of this invention can obtain a thin and smooth thermoelectric film.

[0038] Thermoelectric performance testing: Figure 3 The temperature-dependent thermoelectric properties of the flexible thermoelectric thin film prepared in Example 1 are shown in the graph. The results indicate that at 300 K, the film exhibits a high conductivity of 850 S / cm and a Seebeck coefficient of 103 μV / K, suggesting it is a p-type thermoelectric material. With increasing temperature, the Seebeck coefficient of the film increases within the range of 300-420 K, reaching a maximum of approximately 162 μV / K near 420 K. The conductivity of the film gradually decreases with increasing temperature. The calculated power factor value shows a pattern of first increasing and then decreasing with rising temperature, starting from 901 μW / mK at room temperature. 2 It reaches a maximum value of 1581 μW / mK at 420 K. 2 .

[0039] Performance cycle stability test: Figure 4 The results of the performance cycle stability test of the flexible thermoelectric thin film prepared in Example 1 show that after the film is bent around a 5 mm radius rod 1000 times, the conductivity remains at 95% of the original value and the Seebeck coefficient remains at 98% of the original value, demonstrating excellent flexibility.

[0040] The preparation method of the high-performance flexible thermoelectric thin film in Example 2 includes the following steps:

[0041] (1) Preparation of thermoelectric materials:

[0042] The molar composition of the chalcogenide thermoelectric material is represented by the chemical formula AgSbTe2. Its preparation method includes the following steps: using Ag, Sb, and Te elements of 4N purity as raw materials, weigh and mix them uniformly according to the required weight in a glove box filled with inert gas; loading the uniformly mixed material into a pre-cleaned 9mm aperture quartz tube, and evacuating the quartz tube to a vacuum of 1.0 × 10⁻⁶. -3After Pa, the mixture was sealed with an oxyhydrogen flame. The quartz tube containing the mixture and sealed was placed in a swaying furnace and slowly heated to 850°C at a heating rate of 1°C / min. The temperature was then maintained for 10 hours while swaying. After melting, the tube was cooled to room temperature with the furnace within 20 hours. The quartz tube was then removed and broken to obtain AgSbTe2 bulk thermoelectric material.

[0043] (2) The AgSbTe2 bulk thermoelectric material was crushed and ground into powder using a ball mill at a speed of 350 r / min and a mixing time of 4 h. The powder particles were less than 5 μm, thus obtaining AgSbTe2 thermoelectric material powder.

[0044] (3) The obtained AgSbTe2 thermoelectric material powder and PTFE binder are mixed evenly with a mixer to obtain mixture A, wherein the proportion of PTFE binder added to mixture A is 2wt%.

[0045] (4) Mix A in a planetary ball mill for 5 minutes, with the speed controlled at 300 r / min, to fiberize the polytetrafluoroethylene in the PTFE binder into long fibers with a diameter of 1-100 nm and a length of 10-20 μm, to obtain fiberized mixture B.

[0046] (5) The obtained fibrous mixture B is passed through a vertical hot press roller at 80°C on a vertical roller mill and extruded under a pressure of 20t to obtain a thermoelectric film with a thickness of 350μm.

[0047] (6) The thermoelectric film obtained in step (4) is further passed through a horizontal hot rolling mill at 130°C and rolled multiple times under a pressure of 45t to form a flexible thermoelectric film of Example 2 with a thickness of 60μm.

[0048] Morphology test: The cross-section of the flexible thermoelectric film of Example 2 was observed using a scanning electron microscope (SEM). It can be seen that the polytetrafluoroethylene has been fiberized into long fibers with a diameter of less than 100 nm and a length of about 20 μm. This long fiber structure ensures the toughness and tensile strength of the thermoelectric film.

[0049] Height distribution: The height distribution of the flexible thermoelectric thin film prepared in Example 2 was measured using atomic force microscopy (AFM), and its average surface roughness was found to be 31 nm.

[0050] Thermoelectric Performance Testing: The temperature-dependent thermoelectric performance results of the flexible thermoelectric thin film prepared in Example 2 show that at 300 K, the film has a conductivity of 200 S / cm, exhibiting high conductivity; the Seebeck coefficient is 230 μV / K, indicating that the film is a p-type thermoelectric material. With increasing temperature, the film's conductivity decreases in the range of 300-380 K. With increasing temperature, the Seebeck coefficient gradually increases, reaching a maximum of approximately 268 μV / K near 380 K. The calculated power factor value shows an increasing trend with rising temperature, from 1058 μW / mK at room temperature. 2 It reaches a maximum value of 1176 μW / mK at 380 K. 2 .

[0051] Cyclic stability test: The results of the cyclic stability test of the flexible thermoelectric film prepared in Example 2 show that after the film is bent around a 5 mm radius rod 1000 times, the conductivity remains at 92% of the original value and the Seebeck coefficient remains at 97% of the original value, showing excellent flexibility.

[0052] The preparation method of the high-performance flexible thermoelectric thin film in Example 3 includes the following steps:

[0053] (1) Preparation of thermoelectric materials:

[0054] The molar composition of chalcogenide thermoelectric materials is represented by the chemical formula Cu. 25 As 35 Se6Te 34 The preparation method includes the following steps: using Cu, Ag, Sb, and Te of 4N purity as raw materials, weighing and mixing each raw material according to the required weight in a glove box filled with inert gas; loading the homogeneous mixture into a pre-cleaned 9mm aperture quartz tube, and evacuating the quartz tube to 1.0×10⁻⁶ mm. -3 After Pa, the mixture was sealed using an oxyhydrogen flame. A sealed quartz tube containing the mixture was placed in a oscillating furnace and slowly heated to 850°C at a rate of 1°C / min, holding at this temperature for 10 hours while oscillating. After melting, the temperature was lowered to 650°C, and the quartz tube was quickly immersed in water for quenching. Once the thermoelectric material detached from the quartz tube wall, the tube was immediately placed in an annealing furnace preheated to 140°C and held for 2 hours for annealing. After the annealing furnace temperature slowly decreased to room temperature, the quartz tube was removed and broken to obtain Cu. 25 As 35 Se6Te 34 Bulk thermoelectric materials;

[0055] (2) Cu 25 As 35 Se6Te 34The bulk thermoelectric material was pulverized and ground into powder using a ball mill at a speed of 450 r / min and a mixing time of 6 h. The powder particles were smaller than 5 μm, yielding Cu. 25 As 35 Se6Te 34 Thermoelectric material powder;

[0056] (3) The obtained Cu 25 As 35 Se6Te 34 Thermoelectric material powder and PTFE binder are mixed evenly using a mixer to obtain mixture A, wherein the proportion of PTFE binder added to mixture A is 5 wt%.

[0057] (4) Mix A in a planetary ball mill for 5 minutes, with the speed controlled at 280 r / min, to fiberize the polytetrafluoroethylene in the PTFE binder into long fibers with a diameter of 1-100 nm and a length of 10-20 μm, to obtain fiberized mixture B.

[0058] (5) The obtained fibrous mixture B is passed through a vertical hot press roller at 100°C on a vertical roller mill and extruded under a pressure of 25t to obtain a thermoelectric film with a thickness of 150μm.

[0059] (6) The thermoelectric film obtained in step (4) is further passed through a horizontal hot rolling mill at 120°C and rolled multiple times under a pressure of 30t to form a flexible thermoelectric film of Example 3 with a thickness of 20μm.

[0060] Morphology test: The cross-section of the flexible thermoelectric film of Example 3 was observed using a scanning electron microscope (SEM). It can be seen that the polytetrafluoroethylene has been fiberized into long fibers with a diameter of less than 100 nm and a length of about 20 μm. This long fiber structure ensures the toughness and tensile strength of the thermoelectric film.

[0061] Height distribution: The height distribution of the flexible thermoelectric thin film prepared in Example 3 was measured using atomic force microscopy (AFM), and its average surface roughness was found to be 35 nm.

[0062] Thermoelectric Performance Testing: The temperature-dependent thermoelectric performance results of the flexible thermoelectric thin film prepared in Example 3 show that at 300 K, the film's conductivity is 9.24 S / m and the Seebeck coefficient is 523 μV / K, indicating that the film is a p-type thermoelectric material. With increasing temperature, the film's conductivity increases in the range of 300-420 K, reaching a maximum of approximately 98.15 S / m near 420 K. The Seebeck coefficient gradually decreases with increasing temperature. The calculated power factor value thus shows an increasing trend with rising temperature, from 2.52 μW / mK at room temperature. 2It reaches a maximum value of 22.36 μW / mK at 420 K. 2 .

[0063] Cyclic stability test: The results of the cyclic stability test of the flexible thermoelectric film prepared in Example 3 show that after the film is bent around a 5 mm radius rod 1000 times, the conductivity remains at 93% of the original value and the Seebeck coefficient remains at 99% of the original value, showing excellent flexibility.

[0064] The preparation method of the high-performance flexible thermoelectric thin film in Example 4 includes the following steps:

[0065] (1) Preparation of thermoelectric materials:

[0066] The molar composition of the chalcogenide thermoelectric material is represented by the chemical formula Ag₂Te. Its preparation method includes the following steps: using Ag and Te elements of 4N purity as raw materials, weighing and mixing them uniformly according to the required weight in a glove box filled with inert gas; loading the uniformly mixed material into a pre-cleaned 9mm aperture quartz tube, and evacuating the quartz tube to a vacuum of 1.0 × 10⁻⁶. -3 After Pa, the mixture was sealed with an oxyhydrogen flame. The quartz tube containing the mixture and sealed was placed in a swing furnace and slowly heated to 950°C at a heating rate of 1°C / min. The temperature was then maintained for 10 hours while swinging. After melting, the mixture was cooled to room temperature in the furnace. The quartz tube was then removed and broken to obtain Ag2Te bulk thermoelectric material.

[0067] (2) The Ag2Te bulk thermoelectric material was crushed and ground into powder using a ball mill at a speed of 520 min and a mixing time of 10 h. The powder particles were less than 5 μm, thus obtaining Ag2Te thermoelectric material powder.

[0068] (3) The obtained Ag2Te thermoelectric material powder and PTFE binder are mixed evenly with a mixer to obtain mixture A, wherein the proportion of PTFE binder in mixture A is 10wt%.

[0069] (4) Mix A in a planetary ball mill for 5 minutes, with the speed controlled at 280 r / min, to fiberize the polytetrafluoroethylene in the PTFE binder into long fibers with a diameter of 1-100 nm and a length of 10-20 μm, to obtain fiberized mixture B.

[0070] (5) The obtained fibrous mixture B is passed through a vertical hot press roller at 100°C on a vertical roller mill and extruded under a pressure of 25t to obtain a thermoelectric film with a thickness of 150μm.

[0071] (6) The thermoelectric film obtained in step (4) is further passed through a horizontal hot rolling mill at 120°C and rolled multiple times under a pressure of 30t to form a flexible thermoelectric film of Example 4 with a thickness of 20μm.

[0072] Morphology test: The cross-section of the flexible thermoelectric film of Example 4 was observed using a scanning electron microscope (SEM). It can be seen that the polytetrafluoroethylene has been fiberized into long fibers with a diameter of less than 100 nm and a length of about 20 μm. This long fiber structure ensures the toughness and tensile strength of the thermoelectric film.

[0073] Height distribution: The height distribution of the flexible thermoelectric thin film prepared in Example 4 was measured using atomic force microscopy (AFM), and its average surface roughness was found to be 43 nm.

[0074] Thermoelectric Performance Testing: The temperature-dependent thermoelectric performance results of the flexible thermoelectric thin film prepared in Example 4 show that at 300 K, the film's conductivity is 400 S / cm; the Seebeck coefficient is -110 μV / K, indicating that the film is an n-type thermoelectric material. With increasing temperature, the film's conductivity gradually decreases in the range of 300-400 K. With increasing temperature, the film's Seebeck coefficient shows an increasing trend, reaching a maximum value of approximately -120 S / cm near 400 K. The calculated power factor at room temperature is 484 μW / mK. 2 .

[0075] Cyclic stability test: The results of the cyclic stability test of the flexible thermoelectric film prepared in Example 4 show that after the film is bent around a 5 mm radius rod 1000 times, the conductivity remains at 93% of the original value and the Seebeck coefficient remains at 99% of the original value, showing excellent flexibility.

Claims

1. A method for preparing a high-performance flexible thermoelectric thin film, characterized in that, Includes the following steps: (1) The bulk thermoelectric material is crushed and ground into powder using a planetary ball mill. The rotation speed of the planetary ball mill is 250-520 r / min, the mixing time is 3-10 h, and the powder particles are less than 5 μm to obtain thermoelectric material powder; the thermoelectric material is a sulfur-based thermoelectric material, and the sulfur-based thermoelectric material is Bi 0.5 Sb 1.5 Te3, AgSbTe2, Cu 25 As 35 Se6Te 34 One of Ag2Te; (2) The obtained thermoelectric material powder and PTFE binder are mixed evenly in a mixer at a speed of 100-10000 r / min for 0.5-30 min to obtain mixture A, wherein the proportion of PTFE binder in mixture A is 0.5-10 wt%. (3) Mix A in a planetary ball mill for 5-10 min, with the speed controlled at 200-300 r / min, to fiberize the polytetrafluoroethylene in the PTFE binder into long fibers with a diameter of 1-100 nm and a length of 10-20 μm, to obtain fiberized mixture B; (4) The obtained fibrous mixture B is extruded on a vertical roller mill through a vertical hot press to obtain a thermoelectric film with a thickness of 300-500 μm; (5) The thermoelectric film obtained in step (4) is further rolled into a flexible thermoelectric film with a thickness of 20-150 μm by a horizontal hot rolling roller.

2. The method for preparing a high-performance flexible thermoelectric thin film according to claim 1, characterized in that, In step (2), the temperature inside the mixer is 5-45℃.

3. The method for preparing a high-performance flexible thermoelectric thin film according to claim 2, characterized in that, In step (2), the temperature inside the mixer is 5-30℃.

4. The method for preparing a high-performance flexible thermoelectric thin film according to claim 1, characterized in that, In step (4), the temperature of the two vertical hot press rollers is 20-100℃.

5. The method for preparing a high-performance flexible thermoelectric thin film according to claim 1, characterized in that, In step (5), the temperature of the two horizontal hot rolling rolls is 100-150℃.

Citation Information

Patent Citations

  • Preparation method of high-strength and high-performance composite thermoelectric material

    CN111341902A

  • Thermoelectric conversion material and method for manufacturing same

    WO2013141065A1